Ectopic activation of the rice NLR heteropair RGA4/RGA5 confers resistance to bacterial blight and bacterial leaf streak diseases. (18th August 2016) - Hutin, Mathilde; Césari, Stella; Chalvon, Véronique; Michel, Corinne; Tran, Tuan Tu; Boch, Jens; Koebnik, Ralf; Szurek, Boris; Kroj, Thomas
Summary: Bacterial blight (BB) and bacterial leaf streak (BLS) are important diseases in Oryza sativa caused by Xanthomonas oryzae pv. oryzae ( Xoo ) and Xanthomonas oryzae pv. oryzicola ( Xoc ), respectively. In both bacteria, transcription activator‐like (TAL) effectors are major virulence determinants that act by transactivating host genes downstream of effector‐binding elements (EBEs) bound in a sequence‐specific manner. Resistance to Xoo is mostly related to the action of TAL effectors, either by polymorphisms that prevent the induction of susceptibility ( S ) genes or by executor ( R ) genes with EBEs embedded in their promoter, and that induce cell death and resistance. For Xoc, no resistance sources are known in rice. Here, we investigated whether the recognition of effectors by nucleotide binding and leucine‐rich repeat domain immune receptors (NLRs), the most widespread resistance mechanism in plants, is also able to stop BB and BLS. In one instance, transgenic rice lines harboring the AVR1‐CO39 effector gene from the rice blast fungus Magnaporthe oryzae, under the control of an inducible promoter, were challenged with transgenic Xoo and Xoc strains carrying a TAL effector designed to transactivate the inducible promoter. This induced AVR1‐CO39 expression and triggered BB and BLS resistance when the corresponding Pi‐CO39 resistance locus was present. In a second example, the transactivation of an auto‐active NLR by Xoo‐ delivered designer TAL effectors resulted in BB resistance, demonstrating that NLR‐triggered immune responses efficiently control Xoo . This forms the foundation for future BB and BLS disease control strategies, whereupon endogenous TAL effectors will target synthetic promoter regions of Avr or NLR executor genes. Significance Statement: Here we report that rice immune receptors of the NLR class confer efficient resistance against two bacterial pathogens, Xanthomonas oryzae pv. oryzae and Xanthomonas oryzae pv. oryzicola . We suggest that NLRs and Avr proteins can be engineered for broad spectrum and sustainable resistance to these bacterial pathogens.